Pengaruh Total Aktiva, Capital Adequacy Ratio (CAR), Finance To Deposit Ratio (FDR) Dan Non Performing Financing (NPF) Terhadap Return On Assets (ROA) Bank Umum Syariah Di Indonesia Periode 2010-2014 - Okyviandi Putra Erlangga; Imron Mawardi (Universitas Airlangga, 2016)
The purpose of this study is to analyze the impact of the variables firm size, liquidity, capital adequacy and financing fraud on Sharia Bank profitability in Indonesia by January 2010 until December 2014 period. Research using purposive sampling method for taking samples. Data obtained based on Bank of Indonesia published via Website realtime, obtained 60 samples.Research variables consisted of four independent variables and 1 dependent variable. Data analysing technique to answer research problem and examine research hypothesis using Double Linear Regression Analysis that supported by SPSS Statistics version 20 application.Based on the research, known that the effect of firm size (asset total), Liquidity (FDR), financing fraud (NPF) on Sharia Bank profitability partially significant. Meanwhile, the effect of capital adequacy (CAR) on Sharia Bank profitability not too significant.